Anticonvulsant long-term and rescue medication: The children's perspective. (September 2020) - Woltermann, Sarah; Jeschke, Sarah; Herziger, Birthe; Müller, Ruth Melinda; Kiess, Wieland; Bertsche, Thilo; Bertsche, Astrid; Neininger, Martina Patrizia
Abstract: Background: Little is known about children's perspectives and attitudes towards their long-term and rescue anticonvulsant medication. Methods: We interviewed paediatric patients aged 6–18 years in two university hospitals concerning their anticonvulsant treatment based on a structured questionnaire. We also asked them to draw a picture titled "Me and my medication". Results: We interviewed 100 patients with anticonvulsant long-term medication. 87/100 patients considered their medication to be helpful. 66/100 patients gave an explanation on why a regular medication intake is important, e.g. " Reduction/prevention of seizures ", " Otherwise I have to go to hospital", "I don't want to die" or "Kill the virus which is causing epilepsy" . Of 92 patients with a prescribed rescue medication, 22 (24%) did not know about it. Of the remaining 70, 39 (56%) stated they always carry it with them. When asked to imagine being the physician and to inform about the medication, the children would use illustrative (e.g. brochures) or demonstration material (e.g. " real tablets ") to aid their consultation (47/100). 55/100 would stress the necessity of a regular intake. 52 participants drew a picture related to the given topic. Of those, only 1 depicted rescue medication. Conclusion: Paediatric patients mostly have a positive attitude towards their medication. However, misconceptions exist and participants expressed the desire for more interactive support in the medical counselling. Children are not sufficiently aware of their rescue medication in everyday life. Consequently, physicians should consider the children's needs in their consultations and put more focus on potentially life-saving rescue medication. Highlights: Paediatric patients with epilepsy considered their medication to be helpful. 66% of the patients had explanations why they should take the medication regularly. Every fourth patient with a prescribed rescue medication did not know about it. Almost 50% desired visual aids or demonstration material in medication consultation. As a physician, the children would stress the necessity of a regular drug intake.